Comprehensiveness of online sources for patient education on otosclerosis - Cırık, Ahmet Adnan; Yiğit, Yeşim Esen; Tekin, Ahmet Mahmut; Duymaz, Yaşar Kemal; Şahin, Şamil; Erkmen, Burak; Topsakal, Vedat (Frontiers in Surgery, 2024)
Purpose This study aimed to assess the readability indices of websites including educational materials on otosclerosis. Methods We performed a Google search on 19 April 2023 using the term “otosclerosis.” The first 50 hits were collected and analyzed. The websites were categorized into two groups: websites for health professionals and general websites for patients. Readability indices were calculated using the website https://www.webfx.com/tools/read-able/. Results A total of 33 websites were eligible and analyzed (20 health professional-oriented and 13 patient-oriented websites). When patient-oriented websites and health professional-oriented websites were individually analyzed, mean Flesch Reading Ease scores were found to be 52.16 ± 14.34 and 46.62 ± 10.07, respectively. There was no significant difference between the two groups upon statistical analysis. Conclusion Current patient educational material available online related to otosclerosis is written beyond the recommended sixth-grade reading level. The quality of good websites is worthless to the patients if they cannot comprehend the text.